Safeguarding Linguistic Heritage: Policy, Education, and Community-Based Strategies for the Development and Protection of Maluku’s Local Languages - Maspaitella, Martha; Afdhal, Afdhal (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2024)
This study examines the challenges and strategic opportunities in safeguarding Maluku’s local languages as essential cultural heritage and intergenerational knowledge systems. Despite their role as mother tongues and carriers of oral traditions, these languages face rapid decline due to shrinking numbers of active speakers, disrupted transmission processes, limited educational integration, and fragmented policy implementation. Adopting a qualitative approach that combines policy analysis and linguistic ethnography, the research focuses on selected Maluku communities representing varying levels of language vitality. Data were gathered through policy and curriculum document analysis, in-depth interviews with policymakers, educators, elders, and youth, and participant observation of language practices across formal and informal domains. The findings highlight a misalignment between national and regional language policies, inadequate educational implementation, and weak community involvement, collectively accelerating language shift toward Indonesian and foreign languages. Nevertheless, grassroots initiatives , such as school-based programs, community literacy activities, and adat-driven revitalization , offer promising foundations for preservation. The study proposes an integrated model involving policy reform, pedagogical innovation, and community-based strategies to strengthen language vitality. Its novelty lies in the multidimensional framework combining top-down and bottom-up approaches in Maluku, a linguistically rich but understudied region. The study contributes to sociolinguistics, language policy, education, and cultural sustainability scholarship.